Evaluating Sustainable Development solutions quantitatively: Competence modelling for GCE and ESD. (December 2016) - Böhm, Marko; Eggert, Sabina; Barkmann, Jan; Bögeholz, Susanne
To comprehensively address global environmental challenges such as biodiversity loss, citizens need an understanding of the socio-economic fundamentals of human behaviour in relation to natural resources. We argue that Global Citizenship Education and Education for Sustainable Development provide a core set of socio-economic competencies that can be applied to tackle such challenges. As a central concern of this article, we report on the development of a competence model and its use in an empirical study. The study analyses the ability of German students ( n = 268: 232 pupils in senior secondary school and 36 student teachers) to evaluate solutions for real-world Sustainable Development challenges quantitatively. In doing so, we investigate a theoretically described competence dimension, that is, 'Evaluating and Reflecting Solutions Quantitatively-Economically'. A Rasch partial credit model indicates that 'Evaluating and Reflecting Solutions Quantitatively-Economically' can be modelled as a one-dimensional competence. Grade level, general educational performance and high performance in subjects addressing Education for Sustainable Development positively affect 'Evaluating and Reflecting Solutions Quantitatively-Economically' scores. Although applying basic economic insights in a quantitative manner to Sustainable Development challenges is within the mathematical skill set of most students, even older or better-performing students find it difficult to do so. Thus, these findings underscore the need for economic competencies to be incorporated in Education for Sustainable Development and Global Citizenship Education.